WEB BASED DATABASE SECURITY IN INTERNET OF THINGS USING FULLY HOMOMORPHIC ENCRYPTION AND DISCRETE BEE COLONY OPTIMIZATION - Samuel Raj, R. Joshua; Prakash, M. Viju; Prince, T.; Shankar, K.; Varadarajan, Vijayakumar; Nonyelu, Fredi (Malaysian Journal of Computer Science, 2020)
Web applications are utilized on an extensive scale across the globe and it handles sensitive individual information of users. Structured Query Language (SQL) Data Inference (DI) and injection are procedures that abuse a security defenselessness occurring in the database layer of an application. This research article focuses on website page database security with the help of optimization and encryption methods for Web of Things Environments. Initially, the selected queries in webpage application are injected as per Discrete Bee Colony Optimization (DBCO) procedure. After the Proxy filtering, the injection prevention model is utilized, the injected data with various queries of different special characters are utilized. At long last, the attack gets detected depending on the user query with the assistance of query tree mechanism. Besides, an effective Fully Homomorphic Encryption (FHE) encryption is proposed in the study. From the implementation results, it is to be noted that the proposed method achieved 93.56% security level for the prevented webpage implication-based databases. The effect on the businesses must be comprehended to decrease the risk involved in SQL and DI injection assaults.